Caracterização de complexos polieletrolíticos de quitosana/sulfato de condroitina em diferentes condições de pH e tempo de imersão - Fajardo, André Ricardo (2009)
In this work was developed a study about the self-reorganizatjon of polymeric networks based on polyelectrolytes complexes (PEC) ofchitosan (QT) and chondroitin sulfate (SC). These PEC was processed by electrostatic interaction between the charged groups of QT and SC, when these polyelectrolyte are mixing. For this study, was processed PEC of QT (Mv equal to 87 x iO g mol 1 and deacetylation degree of 85 %) and SC (Mv equal to 22 x 1 O g mol 1) that were swelled in buifer solution with different pH values. The swelling characteristie was evaluated by swelling degree parameter. The self-reorganization of polymeric network was performed by WAXS, DSC, TGA techniques and V images, before the PEC samples were previously swell in media with different pH and different time intervais. According to tbe data from the techniques above described was inferred the processed PEC of QTISC show the ability to reorganize its polymeric network when compared with the original processed material. This reorganization has a pH- and time dependen character. It was proposed that these reorganization occur due to the rearrangement ofQT and SC chains before part of SC releasing during the swelling, mainly in buffers with pH near or higher the pKa ofconjugate acid ofQT (PKaQT 6.2). The variations in the media pH causes to polymeric network leave to be formed by electrostatic interactions and pass to be formed by hydrogen bond, originated by QT chains and not released SC chains approximation. This phenomenon increases the material crystallinity and thermal stability when it is compared with the sample not swelled in a media with less pH condition. The pores size also is affected by this self-reorganizatjon according to MEV images. Therefore, this study confirms that material has a interesting pH-sensitive property. It can be pre-treated to exhibit specific characteristics suiting its use in a more specific way. In a subsequent step the influence of factors, ratio QT/SC, concentration of hydrochloric acid (HC1) used in the QT solubilization and pH of buifer in which PEC is swollen, in the variation of the elastic xx;0] =3 -3 modulus in compression (E) of PEC afier swollen, was studied by a complete 2 factorial design. Measurements in a Texturometer were made to determine the E value. The factors hydrochlorjc acid (HC1) used in the solubilization of QT and pH of buifer in which PEC is swollen, as well as the interaction of these two variables were significant to increase of E. Moreover the factor ratio QT/SC proved to be not significam. Another 22 factorial design with duplicate was performed to study the influence ofthe factors, ratio QTISC and pH ofbuffer in which PEC is swollen, in the variation of periodic distances between crystalline regions presem in the QTISC PEC polymer network. Thus, to evaluate the predominance of a ceflain periodic distance, was calculated the ratio between the diffraction signals observed by WAXS analysis of dry PEC afier-swelled. In this factor design both factor studied, as well as their interaction, proved to be significant for the formation of crystalline regions with smaller periodic distance. The factorial designs performed allowed to infer from the information obtained, which can produce QT/SC PEC with distinct propeíes, according to changes in variables. The formed biomaterial will be able to be applied in fliture studies how devices to controlled release or act how scaffold to ceil culture.